Students’ perception on CFS’ Taaruf week insān sejahtera module: a survey on selected art-based departments in CFS IIUM - Shamshi, Asmiza; Idris, Fathiyyatunnur; Mohd Izam, Madihah; Abdul Aziz, Nabilah Diyana; Mohd Isa, Siti Nursadrina; W.M. Affandi, Wan Nurul Afiqah Akmal (Centre for Foundation Studies, International Islamic University Malaysia, 2024)
Insān Sejahtera (IS) module introduces the new students to IIUM aspirations. Among the core values upheld by the concept of SEJAHTERA under this module are the values of Taqwā, Amānah, Accountability, and Justice. These values encourage students to develop leadership qualities, adab, humility, and a caring attitude toward others. Due to the scarcity of studies that discuss students’ perception and daily life incorporation of IS module in CFS IIUM, a preliminary survey was distributed. Thus, this study is conducted with the aims of measuring students’ perceptions on the implementation of IS module during Taʿāruf Programme and investigating the incorporation of IS Module towards students' life in CFS IIUM. To achieve these aims, a questionnaire is distributed to selected art-based students (i.e. HS, BEN, BAR, and IRK) using a convenient sampling from 2023/2024 intake and a mixed-method result analysis is applied. The results show that the IS module effectively instils core principles but needs improvement in leadership development and practical application of knowledge. Students grasp the concept of Khalīfah in leadership but struggle with applying Islamic principles to complex ethical situations and accurately understanding Rahmatan lil ʿalamīn. Student fatigue, concentration problems, and inconsistent content delivery are the main obstacles to effective retention of the IS module. The study's findings, while insightful, are constrained by sampling limitations. Future research should broaden its scope and methodology. To improve the IS module, a multifaceted approach is recommended, focusing on content delivery, practical application, and student support to enhance overall effectiveness and retention. As a conclusion, it is expected that this study will be able to contribute to the development of knowledge and to the effective implementation of IS module in humanising CFS IIUM’s students' life.